Music Listening in Times of COVID-19 Outbreak: A Brazilian Study - Ribeiro, Fabiana Silva; Lessa, João Paulo Araújo; Delmolin, Guilherme; Santos, Flávia H. (Frontiers in Psychology, 2021)
The COVID-19 outbreak required diverse strategies to avoid a healthcare system crisis, and social distance and self-isolation were the most applied. However, these measures can cause anxiety and depression. Music listening was shown to reduce depression symptoms and regulate emotion. Thus, we explored how music was used during the confinement period and whether it has helped individuals, especially those with severe depression symptoms, to deal with social distancing measures. This cross-sectional study included 494 Brazilian respondents aged 18 years and over. Our online survey comprised sociodemographics, COVID-19 related questionnaires, questions regarding musical listening uses during social distancing measures, anxiety, depression, and resilience levels assessment. Respondents with severe depression were increasingly likely to listen to music to feel emotionally better with the situation, to feel comfort, to forget problems, to be energetic, to decrease sad feelings, to relax, to cheer up, to forget concerns, to express feelings, to reduce anxiety, to remind of better times, to relieve boredom, to stimulate mentally, and to ward off stressful thoughts. The exploratory factor analysis identified four types of musical listening functions during social distancing measures: negative mood management, cognitive functioning, positive mood management, and physical involvement. Participants with severe depression revealed significant differences compared to no-depressed participants for the negative mood management factor, which shows the importance of musical listening to regulate their negative emotions. As a conclusion, we can argue that most of our respondents used music listening to cope and regulate their moods during the confinement, especially those who presented severe-depression symptoms.